Self-Access Centre in Teaching Reading and Vocabulary to EFL Learners - Iin Indasari; Nurhaedah Gailea (Journal of English Language Teaching and Cultural Studies, 2021)
This research is aimed to improve students’ reading skill and vocabulary mastery through self-access centre at tenth grade students of SMAN 5 Kota Serang. This research was conducted for three months. This study tries to answer the main questions (1) how is students’ learning process of reading and vocabulary through self-access centre? (2) how is students’ learning achievement of reading and vocabulary through self-access centre? The method used in this research was a classroom action research. The action research was conducted in two cycles. Each cycle was consisted of four steps; planning, implementing, observing, and reflecting. The data were collected through qualitative and quantitative techniques. The qualitative data were collected by analysing the observation. The quantitative data were obtained from the students score in pre-test and post-test. The study showed that there was improvement on students’ reading comprehension and vocabulary mastery. The mean scores are 53.64 for reading pre-test and 64.92 for vocabulary pre-test. The results of post-test in cycle I show 65.12 for reading post-test and 72.96 for vocabulary. In cycle II, students get 70.88 for reading post-test and 76.36 for vocabulary post-test. The result specifies that self-access centre is successful in improving students reading comprehension and vocabulary mastery.